CpDNA-Gene-Sequence-Based Genetic Diversity, Population Structure, and Gene Flow Analysis of Ethiopian Lowland Bamboo (Bambusinea: Oxytenanthera abyssinica (A. Rich.) Munro). (16th June 2021) - Oumer, Oumer Abdie; Tesfaye, Kassahun; Feyissa, Tileye; Yibeyen, Dagnew; Durai, Jayaraman; Hyder, Muhammad Zeeshan
Abstract : Background . As a member of Poaceae and subfamily Bambusoideae, Ethiopian lowland bamboo ( Oxytenanthera abyssinica ) is one of the most important nontimber forest resources or a potential alternative to wood and wood products. Ethiopia contributes 86% of the total area of bamboo on the continent, Africa, and 7% of the world. O. abyssinica in Ethiopia accounts for 85% of the total national coverage of bamboo. Several studies have been performed on the genetic diversity and population structure analysis of various bamboo species throughout the world but almost nothing in Ethiopia and O. abyssinica . Methods . Young fresh leaves of O. abyssinica from thirteen natural lowland bamboo growing areas across the country were collected. DNA was isolated using a modified CTAB DNA isolation method. Three cpDNA gene sequences (matK, ndhF3, and rps16) were used for the study. PCR products were analyzed, purified, and pair-end sequenced to calculate AC/GC content, average number of nucleotide differences ( k ), nucleotide diversity ( π ) and population mutation rates per 100 sites (θ w ), InDel (Insertion-Deletion), DNA divergence, gene flow, and genetic differentiation. Results . Metekel Zone was found to have extremely higher k, π, and θ w . Higher frequency of genetic differentiation was found between Metekel Zone vs. the distant populations. Higher frequency of gene flow was found between Assosa Zone vs. Oromia populations. Kurmuk haplotype from gaps or missing data considered and Bambasi haplotype from not considered has descendants around them. Conclusion . Using sequences of cpDNA genes, populations of O. abyssinica collected in Ethiopia show clear diversity based on their geographic location. Metekel Zone was found to have the most diverse population, Assosa Zone has been found to be the source of evolution of O. abyssinica, and Gambella population shows a difference from other O. abyssinica populations.